Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695